PENGARUH KEDISIPLINAN TERHADAP KINERJA ANGGOTA KEPOLISIAN PADA RESORT KUTAI KARTANEGARA - Adam, Alfan (PREDIKSI, 2013)
Effects on the Performance of Police Disciplinary Resort aquatic mammal.The purpose of this study was to determine whether there are disciplinary effect on the performance of Kutai Police Resort. The analysis tool used is the Simple Linear Regression. census sampling method, with a sample size of 40 people Kutai Police Resort of data obtained through questionnaires.Simple regression analysis results between discipline and performance of member variables equation Y = 2.59 + 0.339 X. Further correlation r value of 0.607. After the results of the analysis are compared with the r table (table critical value) where N = 40 with a significance level of 0.05, it turns out empirical count r is greater than r table (0.607> 0.393). Thus the working hypothesis (hi) be accepted as true and reject the null hypothesis (ho). This means that there is influence between discipline with the performance of members of the Police Resort (POLRES) aquatic mammal.Â